Experimental and three-dimensional finite element method studies on pounding responses of bridge structures subjected to spatially varying ground motions. Issue 1 (January 2017) - He, Li-Xiang; Shrestha, Bipin; Hao, Hong; Bi, Kai-Ming; Ren, Wei-Xin
Pounding and unseating damages to bridge superstructures have been commonly observed in many previous major earthquakes. These damages can essentially attribute to the large closing or opening relative displacement between adjacent structures. This article carries out an experimental study on the pounding responses of adjacent bridge structures considering spatially varying ground motions using a shaking table array system. Two sets of large-scale (1:6) bridge models involving two bridge frames were constructed. The bridge models were subjected to the stochastically simulated ground motions in bi-direction based on the response spectra of Chinese Guideline for Seismic Design of Highway Bridge for three different site conditions, considering three coherency levels. Two types of boundary conditions, that is, the fixed foundation and rocking foundation, were applied to investigate the influence of the foundation type. In addition, a detailed three-dimensional finite element model was constructed to simulate an experimental case. The nonlinear material behavior including strain rate effects of concrete and steel reinforcement is included. The applicability and accuracy of the finite element model in simulating bridge pounding responses subjected to spatially varying ground motions are discussed. The experimental and numerical results demonstrate that non-uniform excitations and foundation rocking can affect the relative displacements and pounding responses significantly.